Hexane extract from Spondias tuberosa (Anacardiaceae) leaves has antioxidant activity and is an anti-Candida agent by causing mitochondrial and lysosomal damages - Bruna Maria Pereira da Costa Cordeiro; Nataly Diniz de Lima Santos; Magda Rhayanny Assunção Ferreira; Larissa Cardoso Corrêa de Araújo; Alexsander Rodrigues Carvalho Junior; Alan Diego da Conceição Santos; Ana Paula de Oliveira; Alexandre Gomes da Silva; Emerson Peter da Silva Falcão; Maria Tereza dos Santos Correia; Jackson Roberto Guedes da Silva Almeida; Luís Cláudio Nascimento da Silva; et al. (BMC, 2018)
Abstract Background Spondias tuberosa is a plant that produces a fruit crop with high economic relevance at Brazilian Caatinga. Its roots and leaves are used in folk medicine. Methods Chemical composition of a hexane extract from S. tuberosa leaves was evaluated by thin-layer chromatography (TLC), high-performance liquid chromatography (HPLC) and 1H nuclear magnetic resonance (NMR). Antioxidant potential was investigated by DPPH and ABTS assays. Antifungal action on Candida species was evaluated determining the minimal inhibitory concentration (MIC50) and putative mechanisms were determined by flow cytometry analysis. In addition, hemolytic activity on human erythrocytes was assessed and the concentration required to promote 50% hemolysis (EC50) was determined. Results Phytochemical analysis by TLC showed the presence of flavonoids, hydrolysable tannins, saponins and terpenes. The HPLC profile of the extract suggested the presence of gallic acid (0.28 ± 0.01 g%) and hyperoside (1.27 ± 0.01 g%). The representative 1H NMR spectrum showed saturated and unsaturated fatty acids among the main components. The extract showed weak and moderate antioxidant activity in DPPH (IC50: 234.00 μg/mL) and ABTS (IC50: 123.33 μg/mL) assays, respectively. It was able to inhibit the growth of C. albicans and C. glabrata with MIC50 of 2.0 and 0.078 mg/mL, respectively. The treatment of C. glabrata cells with the extract increased levels of mitochondrial superoxide anion, caused hyperpolarization of mitochondrial membrane, and compromised the lysosomal membrane. Weak hemolytic activity (EC50: 740.8 μg/mL) was detected. Conclusion The results demonstrate the pharmacological potential of the extract as antioxidant and antifungal agent, aggregating biotechnological value to this plant and stimulating its conservation.